Keterlibatan Sistem MonoamineINVOLVEMENT OF MONOAMINERGIC SYSTEM IN THE ANTIDEPRESSANT-LIKE EFFECT OF Ocimum sanctum (LINN.) LEAVES EXTRACT IN TArgik pada Efek Antidepresan dari Ekstrak Daun Ocimum Sanctum (Linn.) terhadap Model Hewan Tail Suspention Test - Ridho Islamie; Intan Tristianti; Muhammad Helmi; Devyani Diah Wulansari; Havid Ro’is (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Depression is a psychiatric disorder characterized by decreased mood and affects daily activities.The development of herbal ingredients as complementary therapy becomes increasing in line with the number of patients who avoid side effects in conventional treatment.The purpose of this study is to investigate the potential effects of ethanolic extract of Ocimum sanctumL. as an antidepressant as well as evaluate the potential mechanism of action in the monoaminergic system in invivo study.For evaluation of mechanisms of action, mice were treated serotonin synthesis inhibitors (pCPA), non-selective dopamine antagonists (Haloperidol) and selective antagonists D2 dopamine (Sulpiride) as pre-treatment.The Tail Suspension Test(TST)method is used as a standardized test that has generally been used to evaluate the antidepressant effects of a drug compound. The results showed that the ethanolic extract of OcimumsanctumL. has antidepressant effect at the dose of 150 mg/kg.Ethanol extract of OcimumsanctumL. was able to decrease the immobility time in TST mice model significantly when given pre-treatmentwith pCPA (p<0.05) and haloperidol (p<0.05), while sulpiride (p<0.05) inhibits the antidepressant effects of ethanolic extract of OcimumsanctumL. significantly.These results showed that the monoaminergic system especially serotonergic and dopaminergic were involved in the antidepressant-like effects of ethanolic extract of OcimumsanctumL. by involving dopamine receptors and has a role in serotonin synthesis.